(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2026)
The global skincare industry has experienced a significant shift toward eco-conscious and sustainable products, driven by growing consumer awareness of environmental responsibility and skin health. This article explores the rise of eco-friendly skincare products designed for facial care, focusing on their increasing market dominance, the role of media and digital platforms in shaping consumer behavior, and the long-term transformation of the beauty industry. The study highlights how natural ingredients, sustainable packaging, and ethical production practices influence purchasing decisions and brand loyalty. Additionally, the paper examines the impact of social media, influencers, and green marketing strategies in promoting eco-conscious skincare trends. By analyzing current industry developments, this research aims to identify future directions for sustainable skincare innovation and its potential to redefine industry standards on a global scale